2021
DOI: 10.3389/fendo.2021.668193
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Consequences of Neuronal HIF1α-Deficiency in Mediobasal Hypothalamus in Mice

Abstract: ObjectiveThis study aims to investigate whether hypoxia-inducible factor 1α (HIF1α) in the neurons of the mediobasal hypothalamus is involved in the regulation of body weight, glucose, and lipid metabolism in mice and to explore the underlying molecular mechanisms.MethodsHIF1αflox/flox mice were used. The adeno-associated virus that contained either cre, GFP and syn, or GFP and syn (controls) was injected into the mediobasal hypothalamus to selectively knock out HIF1α in the neurons of the mediobasal hypothala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Recent literature evidence has also shown that, in in vivo models, GLUT-4 is present in the brain, particularly in the hypothalamus, a structure that, as is well known, plays an important role in glucose homeostasis and in energy balance [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature evidence has also shown that, in in vivo models, GLUT-4 is present in the brain, particularly in the hypothalamus, a structure that, as is well known, plays an important role in glucose homeostasis and in energy balance [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%